A Thousand and One Afternoons in Chicago - Hecht, Ben, 1894-1964 (Salt Lake City, UT : Project Gutenberg, 2005)
"A Thousand and One Afternoons in Chicago" by Ben Hecht is a collection of literary sketches written during the early 20th century. The work captures the vibrant life of Chicago through a series of insightful and poignant vignettes, reflecting Hecht's experiences and observations as a journalist and writer in the city. The sketches probe into the everyday lives, struggles, and nuances of the city's inhabitants, aiming to reveal the deeper truths embedded in their urban existence. The opening of this collection sets the stage for Hecht's ambitious endeavor to create a literary form of journalism that transcends traditional reporting. It introduces the author$1 (Bs dissatisfaction with mere publicity work and his desire to explore the richness of city life. This section describes Hecht's inspiration and creative process, leading to the birth of "One Thousand and One Afternoons," where he aims to unveil the stories that lie beneath the surface of day-to-day news. Through an illustrative account of his first ideas and aspirations for the project, Hecht illuminates his belief that the essence of literature exists within the fabric of urban experiences$1 (Bsomething he skillfully conveys throughout the subsequent sketches. (This is an automatically generated summary.)s
Release date is 2005-04-01
E-text prepared by Eric Eldred, Clare Elliott, Charles Franks, and the Online Distributed Proofreading Team
Keywords: Hecht, Ben, 1893-1964 -- Homes and haunts -- Illinois -- Chicago; Chicago (Ill.) -- Literary collections